Propofol Inhibits Oxidative Stress-Induced Neuronal Cell Ferroptosis and Promotes Synaptic Plasticity via the AMPK/ SIRT1/PGC-1α Axis - Chen, Rongmin; Zhang, Miao; Lv, Liangce; Yin, Ruqiu (Indian Journal of Pharmaceutical Education and Research, 2024)
Aim/Background Propofol, recognized for its quick and effective action as a hypnotic anesthetic, is frequently utilized in clinical practice. Our research intended to investigate the mechanism by which propofol inhibits neuronal ferroptosis and promotes synaptic plasticity via mitochondrial energy regulation. Materials and Methods Mouse Hippocampal Neurons (HT22) cells were treated with RAS-Selective Lethal 3 (RSL3) and propofol followed by Reactive Oxygen species (ROS) detection. Expression levels of ferroptosis and mitochondrial energy regulation were analyzed. HT22 cells were treated with a Sirtuin 1 (SIRT1) inhibitor before propofol treatment. Level of ROS, Fe2+ and genes expression and synaptic plasticity were measured. Results In the RSL3-Low+propofol cohort, exhibiting a stark contrast to both the mock group and the RSL3-High+propofol group, the administration of propofol notably attenuated the expression of ROS, Cyclooxygenase 2 (COX-2) and Long-chain-fatty-acid-CoA Ligase 4 (ACSL4), while concurrently enhancing the levels of Glutathione Peroxidase 4 (GPX4), Solute Carrier Family 7 Member 11 (SLC7A11), Nuclear Factor-like 2 (NRF2), Ferritin Heavy chain 1 (FTH1), Adenosine 5’-Monophosphate (AMP)-Activated Protein Kinase (AMPK), SIRT1 and PPARγ Coactivator-1 α (PGC-1α). ROS and Fe2+ levels were substantially greater in the Selisistat+propofol group than in the propofol group, whereas SIRT1 and PGC-1α expression levels were considerably less in comparison to the mock and propofol groups. Conversely, the propofol group showed significantly higher levels of AMPK, SIRT1, PGC-1α, Synapsin-1 (SYN1) and PSD-95 compared to the mock group and the Selisistat+propofol group (p <0.05). Conclusion Propofol inhibits oxidative stress-induced neuronal cell ferroptosis and promotes synaptic plasticity via the AMPK/ SIRT1/PGC-1α axis.
Keywords: Ferroptosis; Oxidative stress; Propofol; Synaptic plasticity